Hidrógeno verde: abriendo las puertas a un futuro energético sostenible en el Perú - Aranibar Ramos, Edgar Romario (2024)
The concern for climate change has driven the search for sustainable energy solutions. In this context, green hydrogen stands out as an emerging and promising option, given its carbon-free production and extensive applicability. However, its academic approach at the Peruvian level is still limited. Therefore, the objective is to analyze the potential of green hydrogen in Peru, considering technical, economic, environmental, and regulatory aspects. The study is based on a review of Peru's current energy matrix, identifying its challenges and limitations, and explores the opportunities and advantages that it could offer in the national context, also examining international experiences. It is observed that Peru has a diverse energy matrix but faces challenges in terms of infrastructure, dependence on fossil fuels, and vulnerability to international price fluctuations. Green hydrogen has the potential to harness renewable natural resources and offers economic, environmental, and social benefits, as well as greater energy diversification and security. It is concluded that the successful implementation of green hydrogen in Peru will require addressing technical obstacles, establishing a solid regulatory framework, and ensuring access to affordable financing. International experiences highlight the collaboration between the government, industry, and academic institutions to accelerate the development of these technologies. Additionally, the establishment of regulatory and political frameworks that provide security and promote collaboration is necessary. One limitation of the work is that it briefly addresses the cost aspect of production plants, a potential point for future research.